Analysis of rectangular flexible horizontal piezoelectric cantilever beam base on ANSYS - A. S., Deraman; Niirmel, Ranjanendran; M. R., Mohamad (IOP Publishing, 2020)
This paper presents the analysis of energy harvester by using rectangular flexible piezoelectric cantilever beam in which applied on sea wave. The limitation of blade design is it only focus on single direction flow of sea wave motion. The finite element model is constructed by using ANSYS to optimize the blade design to maximize the output power. The analysis of rectangular flexible piezoelectric design shows the ability to generate variable of electric power from minimum 20 µW up to 141.30 µW, with dimension of width, length, height of piezo is 10 mm, 30 mm, 0.10 mm and amplitude of sea wave surface of 1.5 m respectively.